Nutritional value of Lycium ruthenicum Murr. and its relieving resistance to exercise-induced fatigue - Xing, Xiaoyuan; Ke, Yu (Progress in Nutrition, 2019)
Lycium ruthenicum Murr. has high medicinal value. This paper mainly studied the nutritional value of Lycium ruthenicum Murr. and its alleviating resistance to exercise-induced fatigue. Firstly, the nutritional composition and value of Lycium ruthenicum Murr. were introduced briefly. Then the alleviating resistance of Lycium ruthenicum Murr. to exercise-induced fatigue was analyzed by swimming experiment in mice. The mice were divided into low, medium and high Lycium ruthenicum Murr. groups. and a blank group which took distilled water. Swimming experiment was conducted after 30 days of continuous feeding, and then the changes of blood sugar, lactic acid and glycogen in mice before, after exercise, after exercise and 30 minutes after exercise were compared. The results showed that 30 minutes after exercise, the group with high dose of Lycium ruthenicum Murr. had higher content of blood sugar, hepatic glycogen and muscle glycogen and lower content of lactic acid. The experimental results demonstrate that Lycium ruthenicum Murr. can increase blood sugar, reduce lactic acid content and increase glycogen reserve in mice, which has good alleviating resistance to exercise-induced fatigue.